THE ROLE OF PARENTS IN EDUCATING CHILDREN IN THE DIGITAL AGE - Apdillah, Dicky; Simanjuntak, Cici Rahma Alia; Napitupulu, Celly Naomi Sarah Br; Sirait, Deviana Dewi; Mangunsong, Juliana (Transpublika Publisher, 2022)
Technological advancements are becoming increasingly pervasive in daily life. Children develop at a rapid pace as technology advances, from televisions to computers, smartphones, and digital tablet devices equipped with a variety of applications. Today's children, called by “Generation Alpha,